Kompetensi Profesional Guru Madrasah Di Lingkungan Pesantren: Professional Competence of Madrasah Teachers in the Pesantren Environment - Rusydi Baya'gub (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2016)
Madrasahs within Islamic boarding school environments have long faced stigma as second-class educational institutions, making the development of teachers' professional competence a crucial issue for reshaping public perception and improving educational quality. This article addresses the major theoretical and practical problem of human resource management and academic supervision, which have yet to function optimally in supporting teacher professionalism. The research aims to describe how teachers' professional competence develops through human resource management and academic supervision. A qualitative case study approach was employed at the Miftahul Ulum Suren Ledok Ombo Islamic Boarding School Foundation in Jember (2015), using Miles and Huberman's interactive model for data analysis. The findings reveal that professional competence development is carried out through planning, recruitment, selection, placement, compensation, rewards, training, and development, alongside academic supervision by principals using individual and group techniques. The study concludes that both approaches positively impact teacher professionalism and recommends stronger supervision instruments and more consistent reward and punishment systems. Madrasah di lingkungan pesantren selama ini masih menghadapi stigma negatif sebagai lembaga pendidikan kelas dua, sehingga pengembangan kompetensi profesional guru menjadi isu krusial untuk mengubah persepsi tersebut dan meningkatkan mutu pendidikan. Artikel ini berangkat dari peta besar masalah manajemen sumber daya manusia dan supervisi akademik yang belum optimal dalam mendukung profesionalisme guru di madrasah pesantren. Tujuan penelitian ini adalah untuk mendeskripsikan pengembangan kompetensi profesional guru melalui pendekatan manajemen sumber daya manusia dan supervisi akademik. Penelitian dilakukan dengan pendekatan kualitatif jenis studi kasus di Yayasan Pendidikan Islam Pondok Pesantren Miftahul Ulum Suren Ledok Ombo Jember tahun 2015, menggunakan model analisis interaktif Miles dan Huberman. Hasil penelitian menunjukkan bahwa pengembangan kompetensi profesional guru dilakukan melalui proses perencanaan, rekrutmen, seleksi, penempatan, kompensasi, penghargaan, pelatihan, dan pengembangan, serta supervisi akademik oleh kepala madrasah dengan teknik individual dan kelompok. Kesimpulannya, kedua pendekatan tersebut berdampak positif terhadap profesionalisme guru, dan direkomendasikan agar madrasah memperkuat instrumen supervisi serta konsistensi dalam reward and punishment.